Drug-Related Adverse Events Necessitating Treatment Discontinuation in Pediatric Inflammatory Bowel Disease Patients. Issue 6 (29th September 2022) - Salzmann, Medea; von Graffenried, Thea; Righini-Grunder, Franziska; Braegger, Christian; Spalinger, Johannes; Schibli, Susanne; Schoepfer, Alain; Nydegger, Andreas; Pittet, Valérie; Sokollik, Christiane; ,
Abstract : Objectives: Inflammatory bowel disease (IBD) requires long-term drug therapy in most patients, posing a risk for adverse drug events with the need for discontinuation. In this study, we investigated adverse events (AE) necessitating drug discontinuation in pediatric and adolescent IBD patients. Methods: We used data prospectively collected from IBD patients below the age of 18 enrolled in the Swiss Inflammatory Bowel Disease Cohort Study (SIBDCS), namely demographic variables, medical characteristics, drug treatments, and related AE. We analyzed the frequency, type, and risk factors for AE necessitating drug discontinuation. Results: A total of 509 pediatric IBD patients fulfilled the inclusion criteria of which 262 (51.5%) were diagnosed with Crohn disease (CD), 206 (40.5%) with ulcerative colitis (UC), and 41 (8%) with IBD-unclassified (IBD-U). In total, 132 (25.9%) presented with at least 1 drug-related AE that required drug cessation. Immunomodulators [methotrexate 29/120 (24.2%), azathioprine 57/372 (15.3%)] followed by tumor necrosis factor (TNF)-alpha antagonists [adalimumab 8/72 (11.1%), infliximab 22/227 (9.7%)] accounted for the highest proportions of AE necessitating treatment discontinuation. Treatment schemes with at least 3 concomitant drugs significantly amplified the risk for development of drug-related AE [odds ratio = 2.50, 95% confidence interval (1.50–4.17)] in all pediatric IBD patients. Conclusions: Drug-related AE necessitating discontinuation are common in pediatric and adolescent IBD patients. Caution needs to be taken in the case of concomitant drug use.